Effect of Repetitive Transcranial Magnetic Stimulation on Pain Management: A Systematic Narrative Review - Yang, Seoyon; Chang, Min Cheol (Frontiers in Neurology, 2020)
Recently, clinicians have been using repetitive transcranial magnetic stimulation (rTMS) for treating various pain conditions. This systematic narrative review aimed to examine the use and efficacy of rTMS for controlling various pain conditions. A PubMed search was conducted for articles published until June 7, 2019, in which rTMS was used for pain alleviation. The key search phrase for identifying potentially relevant articles was [repetitive transcranial magnetic stimulation AND pain]. The following inclusion criteria were applied for article selection: 1) patients with pain were included, 2) rTMS was applied for pain management, 3) after rTMS stimulation, follow-up evaluation was performed to assess the reduction in pain. Review articles were excluded. Overall, 1030 potentially relevant articles were located. After reading the titles and abstracts and assessing eligibility based on the full-text articles, 106 publications were finally included. The evidence supports that rTMS is beneficial for treating neuropathic pain of various origins, such as central pain and pain from peripheral nerve disorders, fibromyalgia, and migraine. Data on the use of rTMS for orofacial pain, including trigeminal neuralgia, phantom pain, low back pain, myofascial pain syndrome, pelvic pain, and complex regional pain syndrome, are promising but insufficient to conclude on rTMS efficacy. Further studies are needed to validate the effects of rTMS on pain relief in these conditions. This review will help guide clinicians in making informed decisions regarding whether rTMS is an appropriate option for managing various pain conditions.